Relationship of Husband Support With Pap Smear Action of Fertile Age Women in Munang-Maning Sub-Village West Denpasar Health Center II Work Area - Sari, Ni Wayan Kuslinda; Pramitaresthi, I Gusti Ayu; Antari, Gusti Ayu Ary (Journal of A Sustainable Global South; Vol 6 No 1 (2022): February 2022DO - 10.24843/jsgs.2022.v06.i01.p04, 2022)
Cervical cancer attacks the female reproductive organ and is the highest cause of death in women in Indonesia. Pap-smear test plays an important role as a screening test for cervical cancer. Unfortunately, the coverage of the pap-smear test in Indonesia especially in Bali is still quite low. Improving a husband support is an effort that could be used to deal with this problem. This study aimed to know the correlation between husband support and pap-smear screening action on women at reproductive age in Public Health Center II of West Denpasar. This study was a descriptive correlative study with a cross-sectional approach that involved 134 participants selected by purposive sampling. The data collection was done by using A Medical Outcomes Social Support Survey (MOS-SSS) and pap-smear screening action questionnaires. The Chi-square test showed that p=0,000 (p<0.05), which indicated that there was a correlation between husband support and pap-smear screening action on the women at the reproductive age.